Pulmonary Langerhans Cell Histiocytosis in a young Non-Smoking Female –Too many Rituals spoil the Lung: PLCH in a never smoker female - Shadrach, Benhur Joel; Agnihotri, Diksha; Goel, Rishabh; haran, Hari (Acta Biomedica Atenei Parmensis, 2021)
Pulmonary Langerhans cell histiocytosis (PLCH) is a rare idiopathic cystic interstitial granulomatous lung disease seen almost exclusively in cigarette smokers. It typically occurs between 20-40 years of age and equally distributed among both sexes. Management includes smoking cessation, avoidance of second-hand smoke, and close follow-up. Corticosteroids may be required in those with symptomatic disease with worsening lung function despite smoking cessation and progressive nodular stage of the disease. Here, we report an interesting case of biopsy-proven PLCH in a young never smoker female. Detailed questioning revealed significant exposure to incense smoke, highlighting a rare presentation of non-cigarette smoke-related PLCH. Avoidance of incense smoke combined with oral prednisolone (0.5mg/kg) tapered over 6 months led to complete resolution of symptoms, disappearance of nodules in high resolution computed tomography (HRCT) of the thorax and improvement in lung function.